1998
DOI: 10.1002/j.2161-1882.1998.tb00123.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Issues of Multiracial Students on College Campuses

Abstract: This i s a preliminary study that focuses on multiracial college students' attitudes regarding the challenges they experience on campus. Results of this study highlight counseling issues that affect multiracial college students, and how college counselors' perceptions of diversity need to be broadened in order to accommodate the rapidly growing multiracinl and muftiethnic student population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…Second, findings from this study support that it is important for multiracial families to address issues of race and ethnicity instead of ignoring them or being avoidant of such topics. This idea aligns with Nishimura (), who revealed that multiracial participants reported race issues to be inevitable and expressed a need for racial differences to be addressed, while also supporting Adams (), who found that the level of family support of a child's multiraciality can be connected to the child's level of self‐esteem. Finally, applying some of the previous literature involving coping with microaggressions can be helpful in family contexts.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Second, findings from this study support that it is important for multiracial families to address issues of race and ethnicity instead of ignoring them or being avoidant of such topics. This idea aligns with Nishimura (), who revealed that multiracial participants reported race issues to be inevitable and expressed a need for racial differences to be addressed, while also supporting Adams (), who found that the level of family support of a child's multiraciality can be connected to the child's level of self‐esteem. Finally, applying some of the previous literature involving coping with microaggressions can be helpful in family contexts.…”
Section: Discussionsupporting
confidence: 76%
“…Participants shared sentiments from previous studies (e.g., Nishimura, ; Root, ), which stated that it was a common experience for multiracial people to feel isolated from family members and to feel different from their monoracial family members.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Nishimura () examined the experiences of multiracial students on college campuses by conducting a preliminary study of 16 undergraduate students. Themes from this study suggested that racial issues are consistently present for multiracial individuals.…”
Section: Resultsmentioning
confidence: 99%
“…Suyemoto encouraged therapists to acknowledge that multiracial people can adopt a healthy multiracial identity while balancing differing perspectives and experiences. Nishimura (1998) examined the experiences of multiracial students on college campuses by conducting a preliminary study of 16 undergraduate students. Themes from this study suggested that racial issues are consistently present for multiracial individuals.…”
Section: Methodology and Applicationmentioning
confidence: 99%